Effect of Customised NPK Fertilizer on Soil Properties, Productivity, and Nutrient Use Efficiency of Maize (Zea mays L.) under Two Different Soil Conditions - Nagabovanalli B. Prakash; Shruthi; Mallikarjuna L.; Kadalli G.G.; Sujith G.M. (Journal of the Indian Society of Soil Science, 2023)
Field experiments were conducted in two different soil conditions viz., location 1 and 2 during the rainy season (kharif) of 2017 and 2018, respectively, at V.C. Farm, Mandya, Karnataka, South India to evaluate the response of maize (Zea mays L.) to different levels of customised NPK fertilizers (CF). Results showed that the application of grades of CF on pH and electrical conductivity (EC) did not vary significantly in both locations. Application of higher levels of CF @ 450 kg ha-1 recorded higher available nitrogen (N), phosphorus (P) and potassium (K) in both locations. Application of CF @ 250 kg ha-1 recorded higher agronomic efficiency of P (AEP) and K (AEK) but higher AEN was observed in 450 kg ha-1 of CF in both locations. Higher nutrient requirement of N of 25.81 and 17.34 kg t-1 by maize crop in locations 1 and 2, respectively was recorded with the application of 450 kg of CF. In both locations, a higher nutrient requirement for (6.05 and 4.43 kg P2O5 t-1 in location 1 and 2, respectively) and (14.31 and 20.76 kg K2O t-1 in location 1 and 2, respectively) was recorded with 450 kg of CF. Higher benefit cost ratio of 3.6 was recorded in the treatment received 450 kg ha-1 CF in both locations 1 and 2.